Combinatorial library of primaryalkylammonium dicarboxylate gelators: a supramolecular synthon approach - Sahoo, Pathik; Adarsh, N. N.; Chacko, George E.; Raghavan, Srinivasa R.; Puranik, Vedavati G.; Dastidar, Parthasarathi (Langmuir, 2009)
Following the supramolecular synthon approach, a combinatorial library comprising 35 organic salts derived from 7 dicarboxylic acids (malonic, succinic-, adipic, L-tartaric-, maleic-, phthalic-, and isophthalicacid) and 5 primaryalkyl amines Me-(CH2)(n)-NH2 (n = 11 - 15) was prepared and scanned for gelation. About 66% of the salts in the combinatorial library were found to show moderate to good gelling ability in various polar and nonpolar solvents including commercial fuels such as petrol. The majority of the salts having a rigid, unsaturated anionic backbone (maleate, phthalate, and isophthalate) did not show gelation; only the corresponding hexadecylammonium salts showed gelation. Some of the representative gels were characterized by rheology, small-angle neutron scattering (SANS), optical microscopy (OM), and scanning electron microscopy (SEM). Single-crystal structures of two gelator and two nongelator salts were also discussed in the context of supramolecular synthon and structure-property correlation.

Ferrocene based organometallic gelators: a supramolecular synthon approach - Sahoo, Pathik; Puranik, Vedavati G.; Patra, A. K.; Sastry, P. U.; Dastidar, Parthasarathi (Soft Matter, 2011)
The supramolecular synthon namely primary ammonium dicarboxylate (PAD) synthon has been exploited to generate a new series of salt based low molecular weight gelators (LMWGs) derived from ferrocenedicarboxylic acid (FDCA) and primary amines Me-(CH2)(n)-NH2 (n = 3-15). While most of the salts are capable of forming gels with DMSO and DMF, nearly all of them show a tendency to form gels with at least one of the solvents studied. Structure property correlation based on single crystal and powder X-ray diffraction data in combination with optical-, scanning-, and transmission-electron microscopy reveals that the supramolecular synthon approach adopted herein for designing LMWGs is indeed useful and allows one to get an easy access to a new series of organometallic gelators.

Supramolecular synthon transferability and gelation by diprimary ammonium monocarboxylate salts - Das, Uttam Kumar; Puranik, Vedavati G.; Dastidar, Parthasarathi (Crystal Growth & Design, 2012)
Earlier studies revealed that primary ammonium dicarboxylate (PAD) salts possessed gelling ability, and many such salts displayed a 1D columnar hydrogen bonded network (observed in primary ammonium monocarboxylate (PAM) salts) on either side of the dicarboxylate end of the anion. In the present study, a new series of diprimary ammonium monocarboxyate (DPAM) salts have been prepared with the aim of achieving supramolecular synthon transferability (the same 1D columnar hydrogen PAM bonded network on either side of the diammonium cation) in these salts. Single crystal X-ray diffraction studies revealed that, in 47% of the DPAM salts, such supramolecular synthon transferability indeed took place. Some of the DPAM salts also showed gelation ability. The gels were characterized by DSC, rheology, electron microscopy, and atomic force microscopy. Structure property correlation using single crystal and powder X-ray diffraction data on a selected gel was also attempted.